Education at a glance 2013. OECD indicators (Paris, 2013)
"Education at a Glance: OECD Indicators is the authoritative source for accurate and relevant information on the state of education around the world. It provides data on the structure, finances, and performance of education systems in more than 40 countries, including OECD members and G20 partners.